HEPARIN-LIKE ANTICOAGULANT ACTIVITY OF SULFONATED POLY(ETHYLENE OXIDE) AND SULFONATED POLY(ETHYLENE OXIDE)-GRAFTED POLYURETHANE - HAN, DK; LEE, NY; PARK, KD; KIM, YH; CHO, HI; MIN, BG (ELSEVIER SCI LTD, 1995)
Sulphonated poly(ethylene oxide) (PEO-SO3) and PEO-SO3-grafted polyurethane (PU-PEO-SO3) were prepared by bulk modification and their anticoagulant and heparin-like activities were investigated. Anticoagulant activity measured by activated partial thromboplastin time of PU-PEO-SO3 displayed 2%, whereas that of PEO-SO3 itself reached 14% as compared to free heparin. In addition, the anticoagulant effects of these sulphonated polymers were not due to factor Xa inhibition but mainly thrombin inhibition. From the clotting time measurements using reptilase instead of thrombin and antithrombin III (AT III), PEO-SO3 and PU-PEO-SO3 indicated heparin-like activity which represents both prolonged thrombin time (TT) and normal reptilase time and increased TT in the presence of AT III. Thrombin was also neutralized by sulphonated polymers to a great extent. Therefore, the anticoagulant and heparin-like activities of PEG-SO3 and PU-PEO-SO3 seem to contribute to their improved blood compatibility.
Keywords: BLOOD COMPATIBILITY; PEO; SURFACES; POLYMERS